Strategic plan for Davao Reyer Transport Services, Inc/Davao Metro Shuttle Corp - Josol, Charlene P. (School of Management, University of the Philippines Mindanao, 2011)
The viability of a business is measured by its long-term survival, and its ability to have sustainable profits over a period of time. If a business is viable, it is able to survive for many years, because it continues to make a profit year after year. The longer a company can stay profitable, the better its viability. (Murray, n.d.). Davao Reyer Transport Services, Inc. started its business in 1995 operating as a taxi company. Eventually, it shifted o a bus company in 1996. IN its 15-year operations today the company is often visited by various challenges that occasionally shake its capability. The escalating prices of fuel, spare parts and generally the high cost maintenance among others poses a great danger for the operations to sustain its viability. This study focused on Davao Reyer Transport Services, Inc/Davao Metro Shuttle Corporation operating in five routes in Region XI. The study aims to offer an answer to the declining performance of the subject company and ensure its long-term viability. This was done by assessing its key internal and external factors and proposed initiatives to be undertaken to achieve its goals. Through the input stage which entailed the preparations of the External and Internal Matrices. It was established that the company has a weak internal position and a strong external position which means that the company is doing well in terms of taking the advantage of the external opportunities and avoiding the threats facing the company. In the matching stage which involved a conduct of Strengths-Weaknesses-Opportunities-Threats Analysis and Internal-External Matrix. It was proposed that the company should pursue a hold and maintain goal which indicates a Product Development and Market Penetration strategies. With the help of the Quantitative Strategic Planning Matrix throughout the decision stage, it is highly recommended that company should pursue the following objectives; reassign Field Inspectors back to the Operation Department, Institutionalize Department Policies, Market Penetration and Service Development.